Gut microbiota, behavior, and nutrition after type 1 diabetes diagnosis: A longitudinal study for supporting data in the metabolic control - Traversi, Deborah; Scaioli, Giacomo; Rabbone, Ivana; Carletto, Giulia; Ferro, Arianna; Franchitti, Elena; Carrera, Deborah; Savastio, Silvia; Cadario, Francesco; Siliquini, Roberta; Cerutti, Franco; Durazzo, Marilena (Frontiers in Nutrition, 2022)
Introduction Type 1 diabetes (T1D) risk involves genetic susceptibility but also epigenetics, environment, and behaviors. Appropriate metabolic control, especially quickly after the diagnosis, is crucial for the patient quality of life. Methods This study aimed to produce a quantitative comparison of the behavior, nutrition habits, and gut microbiota composition between the onset and the 1-year follow-up in 35 children with T1D. Results and discussion At follow-up, with the metabolic control, many parameters improved significantly, with respect to the onset, such as glycated hemoglobin (−19%), body mass index (BMI), and also nutritional behaviors, such as normal calorie intake (+6%), carbohydrate intake (−12%), extra portion request (−4%), and meals distribution during the day. Moreover, glycated hemoglobin decrement correlated with both total and rapid absorption carbohydrate intake (Spearman's rho = 0.288, 95% CI 0.066–0.510, p = 0.013), showing as the nutritional behavior supported the insulin therapy efficiency. The next-generation sequencing (NGS) analysis of microbiota revealed abundance differences for Ruminococcus bromii and Prevotella copri (higher at onset, p < 0.001) and the genera Succinivibrio and Faecalibacterium (lower at onset, p < 0.001), as a consequence of nutritional behavior, but it was not the only changing driver. The qRT-PCR analysis showed significant variations, in particular for Bacteroidetes and Bifidobacterium spp. (+1.56 log gene copies/g stool at follow-up, p < 0.001). During the year, in 11% of the patients, severe clinical episodes occurred (hypoglycemic or ketoacidosis). The likelihood of a severe hypoglycemic episode was modulated when the Methanobrevibacter smithii amount increased (odds ratio 3.7, 95% CI 1.2–11.4, p = 0.026). Integrated evaluation, including nutritional behavior and microbiota composition, could be considered predictive of the metabolic control management for children cohort with a recent diagnosis of T1D.